Consensus statement: osteoporosis prevention and treatment in Latin America—current structure and future directions - Albergaria, Ben-Hur (Arch Osteoporos, 2018)
BACKGROUND: Osteoporosis is a common disorder affecting populations worldwide. In Latin America, an aging population combined with limited health care resources result in osteoporosis quickly becoming a condition of considerable magnitude with disproportionate morbidity and mortality. AIM: To review the current state of prevention, diagnosis, and treatment of osteoporosis in Latin America and to develop strategies and recommendations that may be adopted in the region, an expert panel of clinicians and scientists was assembled to develop a consensus statement outlining future directions. METHOD: The panel conducted a comprehensive literature review of publications mainly related to osteoporosis in Latin America, and at an in-person meeting developed a consensus position to address the relevant issues. RESULTS: The epidemiology, burden, diagnosis, and treatment of osteoporosis in the region were discussed with particular attention to issues unique to the region. A series of recommendations were developed encompassing virtually all aspects of the disease, including improved public and health professional awareness, better diagnostic processes, improved access to care, and greater engagement by health policy makers, government, and a wide variety of private organizations. CONCLUSIONS: The panel concluded that a comprehensive approach to osteoporosis prevention and treatment in Latin America is urgently needed.